Pre-operative Difficulty Assessment of Elective Laparoscopic Cholecystectomy: Validation of a Scoring System (Mugda Medical College Journal, 2025)
Laparoscopic cholecystectomy (LC) is performed all over the world, which is now considered as the gold standard procedure for management of cholelithiasis. Despite its safety standard, sometimes surgeons encounter various difficulties during this surgical procedure. A prospective, observational study was conducted in the Department of Surgery, Dhaka Medical College Hospital, Dhaka, Bangladesh, from December 2018 to June 2019, to identify various risk factors and their correlations with likely difficulty in patients admitted for elective laparoscopic cholecystectomy. All the patients were admitted before surgery and routine preoperative procedures were done. The difficulty was predicted by a scoring system that included clinical, biochemical and sonological indicators with a maximum score of 25 and those were compared with per operative findings. A total of 200 individuals were assessed and analyzed. Age>50, BMI >30, history of acute attack, prolonged symptom duration, and previous abdominal surgery showed a statistically significant predictive association. Biochemical predictors also showed a similar trend with elevated WBC, total bilirubin, ALT, AST, and ALP. Radiologically, gall bladder wall thickness, pericholecystic collection, impacted stone, and fibrosed gall bladder were observed as significant factors. A preoperative score £ 5 provided easy dissection, less operating time, and a good outcome while a score of 6 or more was indicative of difficult laparoscopic cholecystectomy. Preoperative scoring and risk stratification can be used to predict difficult laparoscopic cholecystectomy. High-risk patients may be informed beforehand regarding the possibility of conversion to open surgery. Surgeons and hospital administration also may have to schedule the operating time and team appropriately. It also helps surgeons to be aware of probable complications in high-risk patients based on preoperative scoring.Mugda Med Coll J. 2024; 7(2): 102-107